Implementation of Energy-saving Technologies in House construction - E. I. Krupnov; I. A. Zaytseva; S. A. Loginova; A. V. Simagin (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. Over the past decades, heat pumps have gained great popularity due to their advantages in energy efficiency and environmental friendliness, becoming one of the most attractive alternatives to replace traditional heating systems running on fossil fuels. Heat pump efficiency is a decisive factor that should be taken into account when selecting and optimizing a heat pump system. The aim of the study was to evaluate the efficiency of air source heat pumps of the air-to-water system in the climatic conditions typical of the regions of the Central Federal District. Method. To evaluate the efficiency of air source heat pumps, a mathematical model is used that takes into account the multifactorial nature of the process under study. Result. To adequately compare the obtained research results with the passport performance indicators, the transformation coefficient (COP) was used, showing the ratio of the energy received to the expended work. As a result, the method of heating rooms with an air source heat pump with a combined operation mode was recognized as more preferable. Conclusion. Currently, the potential of heat pumps in the field of energy saving and CO2 emission reduction remains largely untapped, which sets the vector for further research.